Kebersyukuran dan Kebermaknaan Hidup pada Mahasiswa - Fauziah Utami Gumilar; Qurotul Uyun (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2009)
This reseach was aimed to examine the relation between gratititude and the meaning of life with proposed hypothesis that the more gratify indviduals, the more meaningful the life would be. Respondents were 110 college students from private university in Yogyakarta. 2 scales utilized tocollect datawereGratitude Scale and Life Regard Index (Battista and Almond,1973). Data then analyzed using product moment statistical method from Pearson.The result show that gratitude was positively correlated with the meaning of life. The higher respondents' level of gratitude the more meaningful the life they experienced so far and vice versa (r = 0,490; p= 0,05).Keywords: Kebermaknaan hidup, kebersyukuran.